Pengaruh Motivasi Dan Pelatihan Terhadap Kinerja Petugas Pengamanan (Aviation Security) Di Bandara Ngurah Rai Denpasar - Yuliana, Dina (Warta Penelitian Perhubungan, 2010)
Research on the impact of motivation and training to aviation security perJurmance in Ngurah RaiAirport Denpasar has "been perfonned. The results showed that the individual motivation has positiveand signifa:ant impact on the performance of aviation security, individual training has positiveand significant impact on the performance of aviation security and both motivation and training havepositive and significant impact of aviation securihJ at the airport. Impact of motivation and trainingmodels for aviation securihJ performance can be seen from the following equation: Y = 0,434 +0,523Xl + 0,482X2Keywords: airport, aviation securihj, motivation, training, performance.